Study on Employee Pressure and its relationship with Employee Attitude at Workplace - Jamaludin, Mohd Fazil; Muhamad, Marlina; Ruslan, Mohd Firdaus; Adzahar, Khairul Azfar; Saharan, Mohd Shafiz; Hazalli, Mohd Hanif (International Journal of Engineering and Technology, 2018)
The objectives of this study are to identify the relationship between employee pressure and employee attitude.Â Technically, pressure is one of the problems faces by an employee in the workplace. This can give a bad impact on an employeeâ€™s that can affect their attitude against performance in the organization.Â Job characteristics and transformational leadership behavior are the constructs represent employee pressure. This study used questionnaires and distributed them to 118 respondents among administration staff of government agency. Result from multiple regression analysis showed that both job characteristics and transformational leadership behavior significantly influences employee attitude. Therefore, employees who feel that they are better job characteristics and transformational leadership behavior by their organization tend to perform better. It can be concluded that employee pressure does have a relationship with employee attitude.